The Effect of the Use of the Independent Teaching Platform on the Mastery of Information Technology of Classroom Teachers in the Implementation of the Independent Curriculum of Elementary School Segugus 5 Trihanggo Sleman - Ningtyas, Hellen Rosalinda Ayu; Rigianti, Henry Aditia (Journal of English Language and Education, 2025)
This study aims to determine the Effect of the Use of the Independent Teaching Platform (ITP) on the Mastery of Classroom Teachers' Information Technology in the Implementation of the Independent Curriculum of Elementary Schools Segugus 5 Trihanggo Sleman. In the current era of globalization, the use of technology-based platforms has become one of the factors that is considered to improve the quality of education and learning in schools through the advancement of Information Technology. The method used in this study is quantitative with a survey approach. The sample of this study consists of 33 classroom teachers at Segugus 5 Elementary School Trihanggo Sleman who have used or have accessed the Independent Teaching Platform (ITP) for the purpose of classroom learning.  The data in this study was collected through observations, interviews and also questionnaires related to the use of the Independent Teaching Platform (ITP) on the mastery of Information Technology for Elementary School Classroom Teachers in Segugus 5 Trihanggo. The data in this study was analyzed using a simple linear regression statistical test, a correlation test, and a determination coefficient test. The results of the study showed that the use of the Independent Teaching Platform (ITP) could affect the mastery of information technology for teachers in group 5 of Trihanggo by 45.1%. It is hoped that these findings can be a reference for the development of education in the digital era and support the implementation of the independent curriculum through the use of the Independent Teaching Platform (ITP) more effectively.